2004
DOI: 10.1590/s0103-50532004000200008
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenes and triterpenoidal glycosides from the fruits of Ilex paraguariensis (Maté)

Abstract: Dos frutos deIlex paraguariensis foram isolados um novo glicosídeo triterpenóide, o ácido rotúndico 3β-O-α-L-arabinopiranosídeo, denominado matesídeo (4), os triterpenos ácido ursólico (1), ácido acetilursólico (2), ácido 23-hidroxi-ursólico (3) e as saponinas ziyu-glicosídeo I (5) e ilexosídeo II (6). As estruturas foram estabelecidas com base em métodos espectroscópicos, principalmente RMN mono-e bidimensional. Os valores de amargor foram determinados para matesídeo e ilexosídeo II e comparados com os valore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 17 publications
6
45
0
5
Order By: Relevance
“…This was confirmed by presence of 47 carbon signals in 13 C-NMR spectrum of this compound (Table 1) of which seventeen were assigned to a pentose and two hexose units and the remaining 30 signals to a triterpenoid skeleton. The signals at 128.49 and 139.26 due to C-12 and C-13, respectively supported the identification of the aglycone as pomolic acid (19α-hydroxy ursolic acid) (39,41) . Acid hydrolysis of compound 5 gave L-arabinose and D-glucose which were identified by comparison with authentic samples.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…This was confirmed by presence of 47 carbon signals in 13 C-NMR spectrum of this compound (Table 1) of which seventeen were assigned to a pentose and two hexose units and the remaining 30 signals to a triterpenoid skeleton. The signals at 128.49 and 139.26 due to C-12 and C-13, respectively supported the identification of the aglycone as pomolic acid (19α-hydroxy ursolic acid) (39,41) . Acid hydrolysis of compound 5 gave L-arabinose and D-glucose which were identified by comparison with authentic samples.…”
Section: Resultssupporting
confidence: 54%
“…Its IR spectrum (KBr) ν max cm -1 exhibited a characteristic bands of hydroxyl group at 3427 cm -1 , ester carbonyl group at 1735 and double bond (C=C) at 1637 cm -1 (39,40) . The 1 H-NMR spectrum of the compound exhibited resonances for protons of the methyl groups of the aglycone part at the range δ 0.84-1.24, proton of olefinic double bond at δ 5.18 and three anomeric protons of the sugar moieties at δ 4.37, 4.48 and 5.23 (40,41) . This was confirmed by presence of 47 carbon signals in 13 C-NMR spectrum of this compound (Table 1) of which seventeen were assigned to a pentose and two hexose units and the remaining 30 signals to a triterpenoid skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…The chromatographic analysis of these active aqueous and hydroethanol extracts of the aerial parts revealed the predominance of compounds with typical behavior of flavonoids (fluorescence before and after sprying with Natural Product Reagent A); terpenoids and saponins were not detected by using the appropriate methodology usually employed in our laboratory (Taketa et al, 2004). After the fractionation of the hydroethanol extract by solvent extraction, the butanol fraction obtained was chromatographed with a silica gel column aiming the isolation and identification of compound 1 which was predominate.…”
Section: Resultsmentioning
confidence: 96%
“…However, in most cases, the studies focus on identifying and/or quantification of terpenes (TAKETA et al, 2000 and2004), saponins (GNOATTO et al, 2005;PIRES et al, 1997;REGINATTO et al, 1999), polyphenols (BRAVO et al, 2007), methylxanthines (FILIP et al, 1998and 2010, REGINATTO et al, 1999 and flavonoids (TARRAGO et al, 2005, FILIP et al, 2010. In a previous study, Pires et al (1997) observed differences in the chemical composition of two species of Ilex (dumosa and paraguariensis), especially related to the concentration of saponins.…”
Section: Introductionmentioning
confidence: 99%